Networks-On-Chip Based on Dynamic Wormhole Packet Identity Mapping Management. (23rd February 2009) - Samman, Faizal A.; Hollstein, Thomas; Glesner, Manfred
Abstract : This paper presents a network-on-chip (NoC) with flexible infrastructure based on dynamic wormhole packet identity management. The NoCs are developed based on a VHDL approach and support the design flexibility. The on-chip router uses a wormhole packet switching method with a synchronous parallel pipeline technique. Routing algorithms and dynamic wormhole local packet identity (ID-tag) mapping management are proposed to support a wire sharing methodology and an ID slot division multiplexing technique. At each communication link, flits belonging to the same message have the same local ID-tag, and the ID-tag is updated before the packet enters the next communication link by using an ID-tag mapping management unit. Therefore, flits from different messages can be interleaved, identified, and routed according to their allocated ID slots. Our NoC guarantees in order and lossless message delivery.